Comparative analysis of in situ versus ex situ perfusion on flow and microcirculation in kidney procurement: research on a porcine model - Foltys, Daniel (BioMed Central, 2013)
BACKGROUND: The first crucial step in transplantation appears to be the effective rinsing of the graft during organ procurement. Even though there is strong suspicion that ex situ perfusion results in better rinsing of the graft, there is no proof for this hypothesis. The aim of this study was to analyse the differences of in situ and ex situ kidney perfusion in a porcine model. METHODS: Standardised multiorgan procurement was performed in 15 German landrace pigs. Perfusion was carried out using histidine–tryptophan–ketoglutarate solution (HTK) under the application of pressure. In one kidney, in situ perfusion via the aorta was carried out while the second kidney received ex situ perfusion via the renal artery (RA). Perfusate flow inside the aorta and the RA was recorded at different pressure steps. In order to visualise the effect on the microcirculation, different coloured microparticles (MPs; 10 μm) were administered via the aorta or RA. Subsequently, frozen sections of the explanted kidneys were analysed histologically and MPs were evaluated quantitatively. RESULTS: Ex situ kidney perfusion resulted in significantly improved flow rates (P<0.0001) compared with in situ perfusion. By applying ex situ perfusion it was even possible to attain physiological flow levels on the RA under the application of external pressure of 150 to 200 mmHg. The amount of MPs was able to highlight the positive impact of ex situ perfusion on microcirculation of the kidney graft (P<0.0001). CONCLUSIONS: The use of MPs represents a valuable tool for quantitative investigation and illustration of kidney perfusion in experimental setups. Additional ex situ perfusion is able to improve the quality of kidney perfusion.